2021
DOI: 10.3390/sym13010146
|View full text |Cite
|
Sign up to set email alerts
|

The Bias toward the Right Side of Others Is Stronger for Hands than for Feet

Abstract: As shown by a series of previous studies, ambiguous human bodies performing unimanual or unipedal actions tend to be perceived more frequently as right-handed or right-footed rather than left-handed or left-footed, which indicates a perceptual and attentional bias toward the right side of others’ body. However, none of such studies assessed whether the relative strength of such a bias differs between the upper and lower limbs. Indeed, given that the prevalence of right-handedness is slightly larger than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 69 publications
8
9
1
Order By: Relevance
“…Results indicated that the lateralized presentation of the stimuli affected both their perceived limb laterality and their perceived spinning direction, although the effect size was larger in the latter (ηp 2 = 0.06) than in the former (ηp 2 = 0.12) case. In line with our previous studies with ambiguous human silhouettes [1][2][3][4][5][6], with the exception of one out of three experiments in [6], the participants' laterality score did not correlate with the percentage ) compared with male participants (M = 35.73%; t 46 = 2.858, p = 0.026) in the RVF, and no difference was observed between male and female participants in the number of figures interpreted as spinning CW in any of the remaining combinations of hemifield of presentation and outstretched limb (all p > 0.22; Supplementary Material Table S8). Finally, female participants showed a statistical trend to perceive a larger number of CW-spinning figures in the leg-outstretched version of the experiment (M = 56.26%) than in the arm-outstretched version of the experiment (M = 40.03%; t 47 = 2.460, p = 0.070) in the RVF, and no difference was observed between the arm-and leg-outstretched version of the experiment in the number of figures interpreted as spinning CW in any of the remaining combinations of hemifield of presentation and participant's sex (all p > 0.08; Supplementary Material Table S9).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Results indicated that the lateralized presentation of the stimuli affected both their perceived limb laterality and their perceived spinning direction, although the effect size was larger in the latter (ηp 2 = 0.06) than in the former (ηp 2 = 0.12) case. In line with our previous studies with ambiguous human silhouettes [1][2][3][4][5][6], with the exception of one out of three experiments in [6], the participants' laterality score did not correlate with the percentage ) compared with male participants (M = 35.73%; t 46 = 2.858, p = 0.026) in the RVF, and no difference was observed between male and female participants in the number of figures interpreted as spinning CW in any of the remaining combinations of hemifield of presentation and outstretched limb (all p > 0.22; Supplementary Material Table S8). Finally, female participants showed a statistical trend to perceive a larger number of CW-spinning figures in the leg-outstretched version of the experiment (M = 56.26%) than in the arm-outstretched version of the experiment (M = 40.03%; t 47 = 2.460, p = 0.070) in the RVF, and no difference was observed between the arm-and leg-outstretched version of the experiment in the number of figures interpreted as spinning CW in any of the remaining combinations of hemifield of presentation and participant's sex (all p > 0.08; Supplementary Material Table S9).…”
Section: Discussionsupporting
confidence: 92%
“…Results indicated that the lateralized presentation of the stimuli affected both their perceived limb laterality and their perceived spinning direction, although the effect size was larger in the latter (η p 2 = 0.06) than in the former (η p 2 = 0.12) case. In line with our previous studies with ambiguous human silhouettes [1][2][3][4][5][6], with the exception of one out of three experiments in [6], the participants' laterality score did not correlate with the percentage of figures interpreted as right-limbed or spinning CW.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, right-handedness might also be fostered by children imitating adult's manual preferences (Fagard and Lemoine, 2006). Similar mechanisms might be involved not only in the development of handedness, but also in the attentional bias toward the right side of others' body observed in both right-and left-handers (Marzoli et al, 2015(Marzoli et al, , 2017a(Marzoli et al, ,b, 2019Lucafò et al, 2016Lucafò et al, , 2021; see also Marzoli et al, 2014), which in turn could account for the left-handers' advantage in fighting and sports (e.g., Groothuis et al, 2013). Although the relative weight of genetic and environmental determinants of handedness has not been established yet, epigenetic effects have been hypothesized at both the molecular (Leach et al, 2014) and the behavioral level (Schmitz et al, 2017), and the same should be true for other instances of functional asymmetries.…”
mentioning
confidence: 99%